Screening for Natural Producers Capable of Producing 1,3-Propanediol from Glycerol - Dian Andriani; Wien Kusharyoto; Bambang Prasetya; Thomas Wilke; Klaus Dieter Vorlop (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2010)
Glycerol is a renewable resource found as the main by-product in the transesterification of triglycerides and fat saponification. Due to the increased production of plant oils, especially palm oil in developing countries, and their larger use by the oleochemical industry, glycerol surpluses are on the world market and this may result in a desrease in glycerol price. As a consequence, biotechnological processes have been developed to convert this substrate into value-added products, such as 1,3-propanediol (1,3-PD). The microbial production of 1,3-PD could be competitive to chemical routes assuming that it is based on cheap raw material and an optimized process. In the screening for 1,3 PD–producing bacteria, raw glycerol as by-product from rapeseed oil processing unit was used as a carbon source compared with commercial glycerol. By using increasing concentration of both glycerols from 50 to 150 g/l, two potential bacteria were obtained from soil samples.BMP 1 was obtained from an enrichment culture using 50 g/l commercial glycerol, while BMR-1 was obtained from an enrichment culture using 100 g/l raw glycerol. The highest conversion yield obtained using the isolateBMP-1 was around 0.62 g 1,3-PD formed per mol glycerol consumed, and 0.73 mol 1,3-PD formed per molgycerol using the isolate BMR-1. No bacteria were obtained from cultures using 150 g/l commercial and rawgycerol, respectively, which indicated that higher concentration of glycerol has inhibition effect. Keywords: 1,3-propanediol, enrichment culture, glycerol, palm oil, screening